2023
DOI: 10.3390/ijms24087540
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelets in Infective Endocarditis

Abstract: Over the last decade, the incidence of infective endocarditis (IE) has increased, with a change in the frequency of causative bacteria. Early evidence has substantially demonstrated the crucial role of bacterial interaction with human platelets, with no clear mechanistic characterization in the pathogenesis of IE. The pathogenesis of endocarditis is so complex and atypical that it is still unclear how and why certain bacterial species will induce the formation of vegetation. In this review, we will analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…For example, the P2Y12 platelet receptor antagonist ticagrelor could couple its potent and well-known antiplatelet role with noticeable antibacterial properties. Furthermore, a recent study based on a mouse animal model reported a pronounced capacity of ticagrelor to eradicate S. aureus bacteremia [ 131 , 132 , 133 , 134 , 135 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the P2Y12 platelet receptor antagonist ticagrelor could couple its potent and well-known antiplatelet role with noticeable antibacterial properties. Furthermore, a recent study based on a mouse animal model reported a pronounced capacity of ticagrelor to eradicate S. aureus bacteremia [ 131 , 132 , 133 , 134 , 135 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It provides insights into the relationships between the A1 domain of VWF multimers, platelets, neutrophils, and NETs under conditions of high and low shear flow (indicated by red and blue arrows, respectively). Abbreviations: AS, aggregation substance; Clf, clumping factor; Ebp, endocarditis- and biofilm-associated pili; FcγR, crystallisable fragment gamma receptor; Fg, ds, double strand; fibrinogen; Fn, fibronectin; FnBP, fibronectin-binding protein; GP, glycoprotei; GspB, Streptococcus gordonii surface platelet B; IgG, immunoglobulin G; IsdB, iron-responsive surface determinant B; PadA, platelet adherence protein A; Sar P, staphylococcal accessory regulator protein; SrpA, serine-rich glycoprotein A; SRR-1, serine-rich repeat glycoprotein 1; SSL5, staphylococcal superantigen-like 5; VWF, von Willebrand factor [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ].…”
Section: Figurementioning
confidence: 99%
“…This concept offers an intriguing explanation. Several studies have confirmed that the endocardium is indeed a modified endothelium [143][144][145][146][147], although there has been some uncertainty about the specifics of endocardial development. E. faecalis can directly colonise different host epithelial surfaces in a variety of animal experimental models.…”
Section: The Role Of the Endocardium And Enterococcal Pathoadaptationmentioning
confidence: 99%
“…The known pathophysiology of IE is one example of how the immune system has a connection with the hemostatic system. The endothelial lining of the heart and its valves are normally resistant to infection with bacteria and fungi and maintain their functions [ 10 , 11 ]. Conversely, the formation of valve vegetation may be induced by a damaged or inflamed endothelium [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%